Volatile components of leaf and flowers of natural mountain sage (Sideritis spp.) taxa from Davraz Mountain, Isparta-Turkey - Sarıkaya, Ayşe Gül; Canis, Serap (Al-Farabi Natl Univ, 2019)
This study was conducted to volatile components of Natural Mountain Sage (Sideritis spp.) in Davraz Mountain of Isparta, Turkey. For this aim, samples of Sideritis condensata (Boiss. & Heldr.) subsp. condensata, S.hispida P. H. Davis, S. libanotica Labill. subsp. linearis ye S. perfoliata L. taxa, which grow naturally in Davraz Mountain, were collected and examined in terms of volatile constituents and their percentiles. As result, 45 different volatile constituents were identified regarding the leaves and flowers of the samples of Sideritis condensata (Boiss. & Heldr.) subsp. condensata and beta-Pinene, 3-Octanole and Limonene were determined as main components. Also, 42 different volatile components were identified for S. hispida P. H. Davis and (E)-2-Hexenal, beta-Myrcene and Caryophyllene were found as main components. 40 different volatile constituents were identified, regarding the leaves and flowers of the samples of S. libanotica Labill. subsp. linearis. (E)-2-Hexenal, 3-Octanole and Limonene were main components for this taxa. 37 different volatile components were identified for S. perfoliata and alpha-Pinene, beta-Pinene and Limonene were found as main components.
Keywords: Sideritis; Davraz Mountain; Volatile components; Isparta; Turkey